The successful trader's guide to money management : proven strategies, applications, and management techniques - Unger, Andrea, 1966- (Wiley trading advantage., 2021)
"The book describes the various operating methods used by traders and professional investors to calculate how much of their capital can be used in individual transactions. Money management is a fundamental aspect for managing risks faced by any trader when operating on the various financial markets. Most operators, in fact, focus on identifying the operational set-ups (entry levels, stop-loss, take profit, trailing-stop) and do not consider the impact, very often decisive, that a proper money management could have on the final results of its operations. Successful traders focus on risk management, avoiding opening positions that are too large with respect to the total capital they have available. Packed with practical examples and with special focus on money management or position-sizing, The Successful Trader's Guide to Money Management offers a comprehensive coverage of the widely practiced investment techniques, examining their strengths and weaknesses and explains the various operating models, in particular, the Fixed Fractional, Fixed Ratio and Percent Volatility models. With respect to portfolio management, it provides a thorough analysis and discussion on the Core Equity, Total Equity and Reduced Total Equity models. The book also offers essential tips for building and designing a trading system, trading on Forex and choosing a broker"--